SPECIFIC DEGRADATION STRUCTURE FEATURES AND MECHANICAL PROPERTIES OF FURNACE AND HEAT POWER EQUIPMENT ELEMENTS AFTER LONG-TERM OPERATION - F. I. Panteleenko; A. S. Snarsky; A. V. Krylenko (Наука и техника)
The paper presents results of investigations on structure and mechanical properties of technological equipment elements made of heat-resistant steels. A scale of chrome and molybdenum steel microstructure degradation based on evaluation of  coagulated carbide size and material mechanical properties (a point from 0-operation without time limits, up to 4-operation prohibition) has been proposed in the paper. It has been  established that an analysis of  steel microstructure directly on equipment elements by means of a portable microscope is an efficient express method for evaluation of equipment condition and structures due to control of material structure degradation rate of a diagnosed object.